The Use of ecfX Gene as a Specific Identification Target of Pseudomonas aeruginosa Isolated from Infected Wounds - Ibrahim Teka; Alsbani, Amal Elfaitori; Hajer Almuaget (AlQalam Journal of Medical and Applied Sciences, 2024)
Pseudomonas aeruginosa is a significant pathogen in medical settings, accounting for 10% to 20% of infections acquired. This oxidase-positive, Gram-negative bacteria is well-known for its ability to cause respiratory problems, wound infections, and pneumonia related to ventilator use especially in individuals with cystic fibrosis. Prompt and precise diagnosis of P. aeruginosa is essential in of the growing antibiotic resistance, particularly of the limited data on resistance patterns in Libyan healthcare settings. This investigation examines the frequency of P. aeruginosa infections in wounds at Misurata Medical Center and tests the effectiveness of RT-PCR, which targets the ecfX gene, in detecting the pathogen. In this study obtained 165 clinical samples were obtained from patients suffering from wound infections, and using both traditional and molecular methods, we were able to identify P. aeruginosa. The study showed that, in comparison to conventional biochemical approaches, RT-PCR targeting the ecfX gene provides a dependable technique for the quick and accurate detection of P. aeruginosa in clinical samples.